Abortion and the politics of motherhood - Luker, Kristin (California series on social choice and political economy., 1984)
This study of the abortion controversy in the United States argues that moral positions on abortion are intimately tied to views on sexual behaviour, the care of children, family life, technology, and the importance of the individual.